An Anti‐Fatigue Design Strategy for 3D Ribbon‐Shaped Flexible Electronics (Adv. Mater. 37/2021). Issue 37 (14th September 2021) - Cheng, Xu; Zhang, Fan; Bo, Renheng; Shen, Zhangming; Pang, Wenbo; Jin, Tianqi; Song, Honglie; Xue, Zhaoguo; Zhang, Yihui
Abstract : Fatigue Life In article number 2102684, Yihui Zhang and co‐workers present an antifatigue strategy to prolong the fatigue life of 3D ribbon‐shaped electronics by switching the metal‐dominated failure to polymer‐dominated. Combined measurements and computations allow establishment of a failure criterion capable of predicting fatigue life under compressions, thereby providing useful guidelines for the design of antifatigue flexible electronics with diverse 3D geometries.